Development of Monopoly Digestive Media Based on Educational Games as Student Learning Resources on Food Digestive System Concept - Rida Oktorida Khastini; Wineng Siti Rohmah; Tiara Putriana (International Journal of Biology Education Towards Sustainable Development, 2022)
The use of learning material is crucial to the learning process. Teachers can communicate knowledge more effectively by using the appropriate media. However, many teachers continue to solely employ uninteresting material, which might negatively affect their students' motivation for studying. Therefore, innovative and fun learning resources, such as learning media containing play elements, are needed. The research aims to develop learning media on food material and digestive systems using Borg and Gall research development (RD) method. The research data was obtained from a product assessment questionnaire using a questionnaire. The research results obtained from the media expert test average score and material expert test were 85%, and the results from the student response test average score were 89%, categorized as very feasible to be used as student learning resources.